2016
DOI: 10.1158/1078-0432.ccr-16-0044
|View full text |Cite
|
Sign up to set email alerts
|

A Therapeutic Her2/neu Vaccine Targeting Dendritic Cells Preferentially Inhibits the Growth of Low Her2/neu–Expressing Tumor in HLA-A2 Transgenic Mice

Abstract: Purpose: E75, a peptide derived from the Her2/neu protein, is the most clinically advanced vaccine approach against breast cancer. In this study, we aimed to optimize the E75 vaccine using a delivery vector targeting dendritic cells, the B-subunit of Shiga toxin (STxB), and to assess the role of various parameters (Her2/neu expression, combination with trastuzumab) in the efficacy of this cancer vaccine in a relevant preclinical model.Experimental Design: We compared the differential ability of the free E75 pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
1
16
0
1
Order By: Relevance
“…In support to our results, a recent study by Tran et al. [ 16 ] reported that E75-based peptide vaccination can inhibit tumor growth only in low HER2 expressing tumors in HLA-A2 + transgenic mice. This and the fact that HER2 expression is known to increase significantly following disease progression in prostate cancer [ 17 ], could account for the inability of E75-specific cytotoxic T lymphocytes, detected in our patients, to exert an effective antitumor immune response with direct clinical impact.…”
supporting
confidence: 93%
“…In support to our results, a recent study by Tran et al. [ 16 ] reported that E75-based peptide vaccination can inhibit tumor growth only in low HER2 expressing tumors in HLA-A2 + transgenic mice. This and the fact that HER2 expression is known to increase significantly following disease progression in prostate cancer [ 17 ], could account for the inability of E75-specific cytotoxic T lymphocytes, detected in our patients, to exert an effective antitumor immune response with direct clinical impact.…”
supporting
confidence: 93%
“…17 Furthermore, it was reported that targeting of tumor antigens to DC by STxB-based delivery system was efficient to elicit efficient antitumor memory CD8 T cells. [28][29][30][31][32] Thus, our results suggest a synergistic effect of combining rapalog with STxBbased vaccines for the induction of antitumor CD8 T cells with T CM polarization.…”
Section: Discussionmentioning
confidence: 59%
“…STxB-OVA is a candidate cancer vaccine obtained by the chemical coupling of OVA to the recombinant non-toxic Shiga toxin B-subunit variant. [28][29][30][31][32] The synthetic HPV-16 E7-derived 15mer peptide (E7 [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] : GQAEPDRAHYNIVTF, G15F)the E7 49-57 peptide (RAHYNIVTF, RF9)the OVA 257-264 peptide (SIINFEKL, SL8)the AH1 6-14 peptide (SPSYVYHQF, AH1) and the Adpgk mutant peptide (ASMTNMELM, AM9) identified as immunodominant antigen recognized by CD8 + T cells from CT26 and MC38, respectively were purchased from JPT Peptide technologies. The adjuvants alpha-galactosylceramide (α-GalCer), CpG and incomplete Freund adjuvant (IFA) were purchased from Funakoshi, InvivoGen and Sigma-Aldrich, respectively.…”
Section: Reagentsmentioning
confidence: 99%
“…The clinical setting in which a cancer vaccine is tested may be of utmost importance, as the same vaccine can induce a clinical response on early-stage vulvar disease, but not on late-stage cancer [4,14]. Although the Her2-Neu cancer vaccine was mainly proposed in patients expressing high levels of Her2/neu in their tumors [15], we have recently demonstrated that an Her2/neu targeting cancer vaccine is more efficient in low Her2/neu expressing tumors, as Her2 downregulates HLA-class I expression [16]. …”
Section: Introductionmentioning
confidence: 99%